Duplication and nuclear envelope insertion of the yeast microtubule organizing centre, the spindle pole body - Rüthnick, Diana; Schiebel, Elmar (Cells, 2018)
The main microtubule organizing centre in the unicellular model organisms Saccharomyces cerevisiae and Schizosaccharomyces pompe is the spindle pole body (SPB). The SPB is a multilayer structure, which duplicates exactly once per cell cycle. Unlike higher eukaryotic cells, both yeast model organisms undergo mitosis without breakdown of the nuclear envelope (NE), a so-called closed mitosis. Therefore, in order to simultaneously nucleate nuclear and cytoplasmic MTs, it is vital to embed the SPB into the NE at least during mitosis, similarly to the nuclear pore complex (NPC). This review aims to embrace the current knowledge of the SPB duplication cycle with special emphasis on the critical step of the insertion of the new SPB into the NE.
Gesehen am 26.04.2019